2017
DOI: 10.1080/10937404.2017.1399306
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan exposure, transformation, and human health effects

Abstract: Triclosan (TCS) is an antimicrobial used so ubiquitously that 75% of the U.S.A. population is likely exposed to this compound via consumer goods and personal care products. In September 2016, TCS was banned from soap products following the risk assessment by the U.S.A. Food and Drug Administration (FDA). However, TCS still remains, at high concentrations, in other personal care products such as toothpaste, mouthwash, hand sanitizer, and surgical soaps. Triclosan is readily absorbed into human skin and oral muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
249
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(260 citation statements)
references
References 184 publications
4
249
0
7
Order By: Relevance
“…TCS is readily absorbed when applied to human tissues. The resulting human tissue levels are comparable with exposure levels used in this current cell study (Weatherly & Gosse, 2017). Additionally, micromolar levels of TCS have been found in human body fluids in several studies (reviewed in Weatherly & Gosse, 2017).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…TCS is readily absorbed when applied to human tissues. The resulting human tissue levels are comparable with exposure levels used in this current cell study (Weatherly & Gosse, 2017). Additionally, micromolar levels of TCS have been found in human body fluids in several studies (reviewed in Weatherly & Gosse, 2017).…”
Section: Introductionsupporting
confidence: 77%
“…However, TCS is still at high concentrations in other consumer products (e.g., toys, kitchenware, etc.). Additionally, micromolar levels of TCS have been found in human body fluids in several studies (reviewed in Weatherly & Gosse, 2017). The resulting human tissue levels are comparable with exposure levels used in this current cell study (Weatherly & Gosse, 2017).…”
Section: Introductionsupporting
confidence: 71%
“…1,2 In addition, toxicological studies have shown that TCS exposure induces physiological perturbations in animals and in humans. 4,5 Recently, a risk assessment undertaken by the US Food and Drug Administration (FDA) revealed that TCS was present in the urine samples of 75% of the US general population, and, in 2016, the FDA banned its use in soap products. 3,5 Over the last 6 years, a number of studies have identified a positive correlation between the urinary TCS level and sensitization to food, aeroallergens, and perturbations in asthmatic patients.…”
mentioning
confidence: 99%
“…4,5 Recently, a risk assessment undertaken by the US Food and Drug Administration (FDA) revealed that TCS was present in the urine samples of 75% of the US general population, and, in 2016, the FDA banned its use in soap products. 3,5 Over the last 6 years, a number of studies have identified a positive correlation between the urinary TCS level and sensitization to food, aeroallergens, and perturbations in asthmatic patients. 1,6,7 In addition, an experimental study has shown that the topical application of TCS enhances allergic response in ovalbumin (OVA)-sensitized mice, 8 suggesting that TCS might play an adjuvant role in the allergic response to environmental allergens.…”
mentioning
confidence: 99%
“…Second, no exposure dose information was available. While TC is absorbed through the skin [32], triclosan-containing toothpaste is likely the main source of urinary triclosan in mothers; infants, however, are unlikely to be directly exposed and toothpaste use likely will not alter infection risk in children. The amount of exposure to triclosan in the household environment through wash products and dish soap use is not quantifiable.…”
Section: Discussionmentioning
confidence: 99%